Media For Language Teaching and Learning in Digital Era - Hikmah, Durratul (International Journal of English Education and Linguistics (IJoEEL), 2019)
Learning a new language is considered as difficult task because it needs more exercises in various skills. Media plays the important role in increasing the learnersâ€™ desire to learn by creating the atmosphere of fun. In this digital era, learning models utilize technology as leaning media to provide wider access and opportunities for students in building their own knowledge. The availability of technology in education enables educators to plan and implement innovative and interactive learning model.Â  The main goal of this paper is to suggest the current media for teaching and learning language in digital era.